Pemetaan di Desa Pancana berbasis QR Code - Nosakros Arya; Asma Amne Ambarwati; Fuad Husain Akbar; Asri Usman; M. Rusydi Alwi; Sudirman Karnay; Muh. Akbar (Universitas Hasanuddin, 2023)
Pancana is a village located in Tanete Rilau District, Barru Regency, South Sulawesi Province. Pancana Village is located on the beach facing the Makassar Strait and has 3 hamlets, namely Cenrapole, Kaworo and Pancana Hamlets. Pancana Village has a population of 3755 with details of Cenrapole Hamlet as many as 1107, Kaworo as many as 1190 and Pancana as many as 1458. There are two tours in Pancana village, namely Fishing Tours and Awu-Awu Beach. One component of Smart Village is Smart Governance which is defined as the ability of the government to make good decisions through the support of information technology and governance. The Smart Governance component consists of public services, village information systems and village fund management. The activities carried out include the village information system, where the village information system is part of the implementation of e-government. Therefore, as a KKN student, the author wants to carry out an activity entitled Mapping in Pancana Village Based on QR Code where administrative maps and tourist point maps will be integrated with the QR Code so that they are directly connected to google maps and the village website. Map making using Arcgis software. With this activity, it is expected to be able to realize Pancana Village which is Smart Governance by highlighting the technology side so that it can make it easier for anyone who wants to access information about Pancana Village.